Emotional intelligence in nursing students - MAASOUMEH BARKHORDARI; PARISA ROSTAMBEYGI (Journal of Advances in Medical Education and Professionalism, 2013)
Introduction: Emotion is fundamental to nursing practice and Emotional Intelligence is considered as an important characteristic of nurses that can affect the quality of their work including clinical decision-making, critical thinking, evidence and knowledge use in practice, etc. The aim of this research was to assess and compare Emotional Intelligence between freshman and senior baccalaureate nursing students at Islamic Azad University of Yazd. Methods: This descriptive, cross-sectional study was performed on a sample of 87 freshmen and senior baccalaureate nursing students at Islamic Azad University of Yazd. The data was collected, using a questionnaire. The questionnaire consisted of two parts; demographic information and the Baron Emotional Quotient Inventory (EQ-i). The data were analyzed through both descriptive and inferential statistics (t-test, and ANOVA). Results: The mean score of emotional intelligence for the freshmen was 282.37±27.93 and for the senior students 289.64±21.13. No significant difference was found between the freshmen and senior students’ score patterns. Conclusion: The findings showed that there was no statistically significant difference between the freshmen and senior students’ scores. However, as emotional intelligence can have a significant role in what one does. So this quality should be given more importance in nursing education.